Penerapan Metode Bermain Peran (Role Playing) Untuk Menangani Anak Yang Mengalami Selective Mutism - Mulyadi, Deden (CV RIFAINSTITUT, 2022)
Children are admitted to Kindergarten and are expected to help develop their social skills. There are children who are easy to socialize, but there are children who have difficulty adapting and communicating while in the school environment, this condition can be said to be a child experiencing Selective Mutism. With the application of the role playing method, it is expected to be able to handle children who experience Selective Mutism. The purpose of this study was to determine whether the role playing method could reduce the symptoms of Selective Mutism in children. This study used a single case experimental design method with the treatment in the form of role playing given to children. The research subject is a 5-year-old boy who attends Kindergarten on Pamulang, South Tangerang. From the research that has been done, the results show that the application of role playing is effective in overcoming children who experience Selective Mutism, where changes in children's behavior are seen such as being able to start interactions with friends, wanting to play with friends, not crying when their mother is left alone at school, and willing to follow all school activities.